Key production parameters for the development of solid lipid nanoparticles by high shear homogenization. (21st October 2019) - Souto, Eliana B.; Doktorovova, Slavomira; Zielinska, Aleksandra; Silva, Amélia M.
Abstract: In this work, we report the development and optimization of solid lipid nanoparticles (SLN) production by a simple, fast, and cost-effective high shear homogenization process. A screening of several solid lipids (Compritol 888 ATO, Precirol ATO 5, Cetyl Palmitate, Dynasan 118, Imwitor 900K, Stearic acid) has been carried out in combination with Poloxamer 188 as the selected surfactant, based on the mean particle size and polydispersity index. The improvement of the physical stability of the SLN dispersions was achieved by the use of a cationic lipid (cetyl trimethylammonium bromide) reaching zeta potential values above +60 mV. Combining the optimized speed and time of shear, monodispersed SLN (PdI < 0.25) under the nanometer range could be produced.